Respostas eletroencefalográficas durante estimulação magnética transcraniana em adultos normais - Almeida, Alexandre Cardozo de (2019)
Electroencephalogram (EEG) is a well-known painless and noninvasive method, measuring real time brain electrical activity. Transcranial Magnetic Stimulation (TMS) it is another noninvasive, painless and safe method, to modulate, by either activating or inhibiting nerve cells activity. TMS has been increasingly used as a tool in neurosciences. However, its basic mechanisms are not fully understood. Simultaneous TMS/EEG recordings are technically challenging, but could bring some missing information. To investigate the effect of TMS in EEG signals of the primary motor cortex area of normal subjects, describing its properties in the time and frequency domain eleven normal subjects were submitted to TMS single pulses during EEG. TMS was also applied to a non-human head model: muskmelon (Cucumis sp.). In the time domain the evoked potentials P60, N100, P190 and N280 were obtained. Frequency domain results showed initially oscillations between 0.5 to 70 Hz. After capacitor recharging time correction, set away from the epochs, oscillations were within 0.5 and 20Hz. Data from other publications were replicated in our population. This information can be useful for motor pathways future studies. TMS capacitors recharge time must be set-up to avoid undesired neuronal activation that could put results in doubt. It is also advisable to the researchers who record TMS/EEG that the recharge time must also be clearly informed in methods section.